Anomalies of Psychopathic Behavior in Naomi Midori's Novel "Patient": A Study of Literary Psychology 1982 and Implications for Learning Indonesian - Fahmaywati; Abdul Aziz Khoiri (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This research is based on the phenomenon of depicting psychopathic behavior in literature, particularly through fictional characters that show the psychological complexity of humans. This study aims to describe the characteristics of psychopathic behavior and reveal the factors causing the formation of psychopathic personality in the character Imelda in the novel Pasien by Naomi Midori. This research applies a descriptive qualitative method with a content analysis design. The approach used is literary psychology. The data sources consist of narrative quotations, dialogues, and descriptions of Imelda’s actions in the novel. The research instrument is a text content analysis guide made based on the indicators of Robert Hare’s psychopathy theory and Sigmund Freud’s personality theory. Data collection techniques were carried out through documentation studies with stages of intensive reading, data identification, data selection, and data organization. Data analysis techniques use content analysis which includes determining the analysis object, focusing on analysis categories, classifying data, interpreting data, and formulating conclusions. The research results show that Imelda depicts twelve psychopathic traits according to Robert Hare’s theory, such as charming speaking ability, egocentric and arrogant, lack of remorse, absence of empathy, manipulative nature, impulsive, need for stimulation, poor emotional control, irresponsibility, early behavioral disorders, and antisocial attitude. In addition, four factors causing the formation of psychopathic behavior were found based on Freud’s theory, namely dominance of the id, weakness of the superego, ego dysfunction, and childhood trauma. The research conclusion affirms that Imelda’s psychopathic behavior is the result of interaction between internal psychological factors and traumatic experiences. Research suggestions are directed to future researchers to use more varied objects, theories, or approaches to enrich literary psychology research.